Penataan Arsip Bidang Penempatan dan Pengembangan Tenaga Kerja Dinas Transmigrasi dan Ketenaga Kerjaan Sumatera Barat - Nurainun, Nurainun; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
Abstract The purpose of this study was to describe how to set up the archive and know the constraints faced in structuring archives in the Field Placement and Workforce Development Department of Transmigration and Manpower of West Sumatra. The method used is descriptive method is the technique of collecting data through direct observation or observation, and interviews with the archivist Field Placement and Workforce Development Department of Transmigration and Manpower of West Sumatra. How to setup the files used in the Field Placement and Transmigration Department of Workforce Development and Employment West Sumatra is the arrangement of files by type of letter, the obstacles encountered in the arrangement is inadequate infrastructure in the field of archives such as filing cabinets, filing cabinets, and a special room for structuring the archive. Keywords: structuring archives; archival strorage;filing cabinets